Tracking teachers experience of adopting my English step to infuse differentiated instruction - Ilza Mayuni; Yinghui Chen; Ni Made Ratminingsih; Tara Mustikaning Palupi; Nurhasanah Halim (Studies in English Language and Education, 2024)
As a post-developmental study, this qualitative research is intended to evaluate teachers continued experience in adopting My English Step (MES) digital learning material and promoting inclusion in Differentiated Instruction (DI) at junior high school (JHS). Nine junior high school teachers with MES experience were selected through focus group interviews. Research data were achieved by transforming recorded interviews into verbatim transcription. Three corresponding flows of activity were conducted during data analysis: data condensation, data display, and conclusion drawing and verification. The consistency of findings was triangulated by comparing findings from interviews to those in documents on teachers adoption of MES in class and the literature review. The first finding shows that experiences have influenced MES-usability and teachers intent to adopt MES. Previously perceived as an English learning platform, MES is now posited as an adaptive digital learning object. This digital educational resource can be modified and adhered to its contextual connection. Next, improvements in content and functionality are requisite for MES to be adhered to in English learning in the enactment of Kurikulum Merdeka (KurMer). The last finding affirmed that teacher modification questioning strategies can promote inclusion when adopting and adhering to MES to KurMer. Future research should explore the extent to which students potential to learn English is improved by adopting MES.